Penistaan Agama atau Perbedaan Pandangan? Kajian Pemikiran Kontroversi Syaykh As Panji Gumilang - Ali Aminulloh; Siti Ngainnur Rohmah; Nurrohman Nurrohman; Dadan Mardani; Ramlan Harun (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Today the virtual world is excited about the controversy regarding the thoughts of Shaykh Al-Zaytun. In fact, differences in understanding and thinking in understanding the text of the verses of the Qur'an and hadith are common. Even from ancient times, there were differences in understanding and thinking. This is proven by the existence of many schools of thought in fiqh and theology. However, currently, these differences in understanding and thinking are used as a tool to justify minority groups who differ from the majority group as a heretical group. The purpose of this research is to explain the thoughts of Shaykh AS Panji Gumilang's controversy about religious blasphemy or differences of opinion. The research method used is qualitative, with normative and empirical approaches. The results of this study state the views of Shaykh AS. Panji Gumilang, which is considered controversial, is a difference of opinion, not a misguidance. This actually exists in the academic realm, so the judgment of social media and religious institutions against Shaykh Al-Zaytun becomes counter-productive to the development of thought that should be turned on. The attitude of freedom of spirit, freedom of thought, and freedom of knowledge needs to be inflamed in Indonesian society, so that they can be more open in accepting different views. It's not easy to blame people for being different from mainstream views, before the facts and scientific basis are clear, and not just dragging them into cases of blasphemy.Keywords: Blasphemy of Religion; Controversy; Difference of Views AbstrakDewasa ini jagat maya sedang heboh dengan kontroversi terkait pemikiran Syaikh Al-Zaytun. Sebenarnya perbedaan pemahaman dan pemikiran dalam memahami teks ayat-ayat Al-qur’an dan hadis adalah hal yang biasa terjadi. Bahkan dari zaman dahulu perbedaan pemahaman dan pemikiran itu sudah ada. Hal ini terbukti dengan adanya banyak madzhab dalam fiqih dan teologi. Namun saat ini perbedaan pemahaman dan pemikiran tersebut dijadikan sebagai alat menjustifikasi kelompok minoritas yang berbeda pendapat dengan mayoritas kelompok sebagai kelompok yang sesat. Tujuan penelitian ini adalah untuk menjelaskan tentang pemikiran kontroversi Syaykh AS Panji Gumilang itu penistaan agama atau perbedaan pandangan? Metode penelitian yang digunakan adalah kualitatif, dengan pendekatan normatif dan empiris. Hasil penelitian ini menyatakan bahwa pandangan-pandangan Syaykh AS. Panji Gumilang yang dianggap kontroversi, merupakan perbedaan pendapat, bukan suatu kesesatan. Hal ini sebenarnya ada pada ranah akademik, maka penghakiman media social dan lembaga keagamaan terhadap Syaykh Al-Zaytun, menjadi kontra produktif dengan pengembangan pemikiran yang seharusnya dihidupkan. Sikap merdeka ruh, merdeka fikir, dan merdeka ilmu perlu digelorakan kepada masyarakat Indonesia, supaya bisa lebih terbuka dalam menerima perbedaan pandangan. Tidak mudah menyalahkan orang karena berbeda dengan pandangan mainstream, sebelum jelas faktanya dan dasar keilmuannya, dan tidak asal menyeretnya pada kasus penistaan agama.Kata Kunci: Penistaan Agama; Kontroversi; Perbedaan Pandangan